Renewable Energy Transition: A Panacea to The Ravaging Effects of Climate Change In Nigeria - Bello*, Usman; Livingstone, Udofia; Abdullahi, Auwal M; Sulaiman, Ibrahim; Yahuza, Khuzaifah M. (Aceh International Journal of Science and Technology, 2021)
Environmental issues linked to climate change and global warming have been at the center stage of discussion all over the world. This is due to their magnitude and a broader scope of consequences. The catastrophic effects of greenhouse gases (GHGs) such as CO2, CO, water vapor, and ozone, coupled with other artificially induced chemicals like CFCs have shifted weather patterns across the globe, thereby threatening the environment unpleasantly. In Nigeria, the unprecedented utilization of fossil-based fuels as the main energy source for electricity, transportation, industrial, agricultural, and domestic purposes is one of the contributory factors of climate change. As a result, air pollution, land spills by oil, and increasing heatwaves negatively impacted the ecosystem by intimidating the environment, counteracting biodiversity, decelerating the economy, and provoking human comfort while simultaneously antagonizing socio-economic growth and sustainable development. Recently, the abrupt seizure of rainfall in northern Nigeria left many farmlands burning while many other places where been wiped out by heavy flooding. These scenarios have heightened food shortage, economic hardship and rendered thousands homeless. Thus, the government needs to intensify the campaign for afforestation by planting many trees to support green conservation of biodiversity and unleash the huge potentials of renewable energy resources in the country, as the plausible options to remediate the lingering energy failure and ravaging effects of climate changes. Therefore, this short review of communications X-rayed some recent devasting incidences caused by climate change, its impacts on various sectors, and the need to explore renewable energy resources in the country.